Availability, Accessibility, and Suitability of Native Flowers from Central Chile to Mastrus ridens, a Parasitoid of Codling Moth - Tania Zaviezo; Alejandra E. Muñoz; Erick Bueno (Insects)
Habitat manipulation through non-crop vegetation management is a strategy in conservation biological control, and using native plants is attractive because they can also help in biodiversity conservation. The potential for nectar provision of 13 flowering species native to Chile, and two introduced, was evaluated considering Mastrus ridens (Hymenoptera: Braconidae). Nectar availability was studied through flower phenology, accessibility through flower and parasitoid morphology, and suitability through longevity when exposed to nectar solutions or cut flowers. Most species had long flowering periods, potentially making nectar available when adults are active, but they differed in nectar accessibility and profitability. Of the 13 native species, nectar was easily accessible for M. ridens in Cistanthe grandiflora, Sphaeralcea obtusiloba, Andeimalva chilensis, and Lycium chilense. None of the nine native species tested with nectar solutions increased longevity, but with cut flowers, parasitoids lived longer with the natives Teucrium bicolor and S. obtusiloba, and the introduced Fagopyrum esculentum, making them candidates for M. ridens conservation. Females lived longer with cut flowers of T. bicolor and S. obtusiloba than with their nectar solutions. In conclusion, using the native flowering species Teucrium bicolor and Sphaeralcea obtusiloba in agroecosystems can serve biological control and biodiversity conservation.